Dasar Pengujin KTUN dalam Kasus Reklamasi Pulau G: Antara Legalitas, Asas Praduga Sah dan Kepentingan Publik - Febri Aditiya Nur Wahid; Hikmatyar Ramadhani Mustofa Ilham; Zahwa Istiqomah Builqis (Journal of Innovative and Creativity, 2025)
This research examines the legal basis for reviewing State Administrative Decisions (KTUN) in the dispute over the reclamation permit for G Island in Jakarta. The case began with the issuance of Jakarta Governor Decree No. 2238 of 2014, which granted a reclamation permit and was later challenged by fishermen and environmental groups for violating regulations and harming coastal communities. This study uses a normative legal research method with statutory, case, and conceptual approaches. The analysis focuses on assessing the conformity of the government’s decision with the principle of legality, the General Principles of Good Governance (AUPB), and environmental regulations. The findings show that the Jakarta Administrative Court (PTUN) annulled the decree for contradicting Law No. 27 of 2007 and Law No. 32 of 2009, as well as for violating AUPB, including legal certainty, transparency, caution, and justice. However, the Supreme Court (MA) took a different stance at the cassation level, emphasizing the presumption of legality (presumptio iustae causa) and rejecting the lawsuit based on procedural deadlines, allowing the decree to remain in force. This contrast demonstrates that PTUN prioritizes legality and public protection, whereas MA places greater emphasis on legal certainty and administrative stability. Overall, this research highlights that KTUN review must balance legality, AUPB, presumption of legality, and public interest to ensure that administrative decisions are not only legally valid but also fair and beneficial for society.